Prevention and treatment of MS: studying the effects of vitamin D - Munger, Kassandra L. (2011)
Observational studies suggest that adequate vitamin D nutrition may reduce the risk of MS and affect the course of the disease. Inherent limitations in these studies, however, preclude a causal interpretation. Randomized controlled clinical trials are the next step to addressing whether vitamin D prevents MS or can favorably affect the course and progression of MS. Here we briefly review the current literature on vitamin D and MS, both as a risk factor and potential treatment for MS with a focus on the issues and challenges in designing prevention and treatment clinical trials.